Fast and high amount of U(VI) uptake by functional magnetic carbon nanotubes with phosphate group - Liu, Yan (2020)
In the present study, PZS-TPP/CNT/Fe3O4 was fabricated by carbon nantubes (CNTs) with polyphosphazene and magnetic particles for application in U(VI) removal. The structure of the synthesized composite was characterized by Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), a vibrating sample magnetometer (VSM), and X-ray photoelectron spectroscopy (XPS). Studies of the effects of pH values, U(VI) concentration, contact time, and adsorption temperature including competing ions and reusability to the uranium adsorption were conducted. The calculated qmax from the Langmuir model was 606.06 mg/g. The possible mechanism was investigated by XPS about the uranium-adsorbed PZS-TPP/CNT/Fe3O4, which revealed that the adsorption capacity was mainly due to the coordination ability of phosphoryl groups and nitrogen atoms in the polyphosphazene skeleton. This new material is promising for separation and safe disposal of radionuclides in water.